Isolated abdominal wall metastasis 42 years after curative surgery for ovarian cancer: A case report - Roland Csorba; Paul Buderath; Marc Ingenwerth; Sa'ed Almasarweh; Zeynep Atas Elfrink (Case Reports in Women's Health)
Despite the rarity of abdominal or chest wall metastases in ovarian cancer patients, reports have described instances of isolated late recurrence at surgical incision sites. We report the case of an 85-year-old woman who present with a massive metastatic tumor on the right anterior abdominal wall 42 years after undergoing a total abdominal hysterectomy and bilateral salpingo-oophorectomy for primary ovarian cancer. The abdominal wall tumor was resected en bloc, and abdominal wall reconstruction was performed using a mesh. Histology revealed a low-grade serous carcinoma.This report highlights the possibility of abdominal wall metastases after prolonged survival following the treatment of ovarian cancer. Surgical excision combined with mesh reconstruction represents an adequate treatment approach for such cases. Caution should be exercised during laparotomy to ensure complete removal of malignant tissue and to prevent parietal dissemination. Long-term follow-up is crucial for ovarian cancer patients, as late recurrences, although rare, can occur even decades after initial treatment.